1974
DOI: 10.1007/bf02451749
|View full text |Cite
|
Sign up to set email alerts
|

Bio-degradation and utilization of silica and quartz

Abstract: Summary. A mesophilic bacterium, Proteus mirabilis, which was known to be able to accumulate monomer silicate ions, a thermophilic bacterium, Bacillus caldolyticus, originating from a habitat with high silica concentrations, and a silicautilizing plant, Equisetum arvense, were all found to produce monomer silica from its polymer. The monomer silica, resulting from the mineralysis of either experimentally polymerized silica, or from quartz, is taken up by P. mirabilis cells, and also by Equisetum, which then de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…This indicates that also temporal degradation of the nanocomposite occurs and could allow kinetic studies with the DCA, since the contrast disappears during remodeling of the cement. The disappearance of the CT signal with time could be explained as a result of the degradation of the outer shell of the silica beads, 23,24 resulting in dilution of the gold nanoparticles. Instead, iron nanoparticles were placed on the inside of the bead, which degrade much slower.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that also temporal degradation of the nanocomposite occurs and could allow kinetic studies with the DCA, since the contrast disappears during remodeling of the cement. The disappearance of the CT signal with time could be explained as a result of the degradation of the outer shell of the silica beads, 23,24 resulting in dilution of the gold nanoparticles. Instead, iron nanoparticles were placed on the inside of the bead, which degrade much slower.…”
Section: Discussionmentioning
confidence: 99%
“…Despite silici cation, the colonies retain some of their original carbon and nitrogen. Active uptake and enrichment of Si by different species of bacteria and cyanobacteria have been reported (Lauwers and Heinen 1974;Heinen and Lauwers 1988). It is possible that the Si in the low-mineralized microbes of the TAG mound may be due to biological uptake.…”
Section: Silica Mineralization (Silici Cation)mentioning
confidence: 98%
“…Studies on morphology and ultrastructure of shark enamel Reif (1973Reif ( ) 1974 ''Handbook of Histopathology and Histochemical Techniques'' is published Culling (1974Culling ( ) 1974 370 MYO devonian boring algae were described Kobluk andRisk (1974) 1974 Fungal osteoclasia: a model of bone resorption Marchiafava et al (1974Marchiafava et al ( ) 1974 Biodegradation and utilization of silica in nature Lauwers andHeinen (1974) 1975 Demineralization of bone matrix: observations using the electron microscope Thorogood andGray (1975) 1975 ''The Study of Trace Fossils'' is published Frey (1975) 1975 Mineral-tetracycline reactions and tetracycines as demineralization agents in bone, teeth and hard tissues Skinner and Nalbandian (1975); Wikesjö et al (1986); Sterrett et al (1997Sterrett et al ( ) 1975 Decalcification techniques in electron microscopy Dietrich andFontaine (1975) 1976 Isolation of 80 million year old mollusc shell proteins Weiner et al (1976Weiner et al ( ) 1976 Demineralization in forensic science Helfman and Bada (1976); Waite et al (1999Waite et al ( ) 1976 Oldest (Upper Silurian) organic remains of boring algae are found Kazmierczak andGolubic (1976) 1976 SEM study on dentin: demineralization results in shrinkage of the dentin structure Garberoglio andBrännström (1976) 1976 ''Forensic Dentistry'' is published Sopher (1976Sopher ( ) 1977 Decalcified bone as a substrate for osteogenesis Nade andBurwell (1977) 1977 Caries and the remineralization phenomena Silverstone (1977…”
Section: Biominerals and Biomineralizationmentioning
confidence: 99%